Transboundary water governance institutional architecture: reflections from Ethiopia and Sudan - Mapedza, Everisto D.; Haileslassie, Amare; Hagos, Fitsum; McCartney, Matthew P.; Awulachew, Seleshi Bekele; Tafesse, T. (2009)
Transboundary water resource governance is premised on equitable water and water-related benefit sharing. Using the case of the Blue Nile (Ethiopia and Sudan), we explore the conceptual issues that need consideration in the crafting of cross-border cooperation within the water sector. First, drawing on global experiences with transboundary water management, we evaluate how upstream and downstream concerns are addressed by transboundary water management institutions. Second, we explore the kinds of institutional design and the issues which need to be considered to result in ?win-win? scenarios for both upstream and downstream users, as well as the mechanisms of benefit sharing negotiated amongst different stakeholders. Third, we examine ways of addressing equity and livelihoods in transboundary institutional arrangements. Finally, we attempt to assess how transboundary institutions can address broader historical, political and economic issues and their implications for sustainable transboundary water governance. This paper raises key issues that need to be addressed in establishing transboundary governance institutions.